PENGUNGKAPAN RISIKO PERUSAHAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016 dan 2017) - Lucia Linear Anggraeni; Wahyu Meiranto (Diponegoro Journal of Accounting, 2019)
This research aims to examine the influence determinant of corporate risk disclosure on manufacturing enterprises listed on Indonesia Stock Exchange (IDX) in 2016 and 2017. In addition, this research also examine whether the size of the company is large, cross listing conducted by the company, a high risk level, the large size of the board  and the high composition of the board that will affect the company in a more complete and detailed risk disclosure. Using the basis of the agency, stakeholder, signaling, and legitimacy  theory related the large company size, the cross listing, the high risk level, the large board size, and the high board composition that make company disclose the risk more detailed.The  population in this research were several manufacturing companies listed on the stock exchange in Indonesia in 2016 and 2017. Then 157 samples were obtained from 300 populations registred on the IDX. The analytical tool  used in this research is multiple regression analysis.The result of this examine show that the firm size, cross listing, board size, and board composition has a positive significant effect to the corporate risk disclosure and the level of risk will not affect corporate risk disclosure. With this result, it can be concluded that the large  size of the company, the cross listing, the large size of the board, the high composition of the board cause the company disclose the risk in more detailed. And the influence of the level of risk on disclosure of company risk maybe because it is influenced by other factors.